2021
DOI: 10.3390/su13137489
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Wine Tourism: An Approach through Social Media Data

Abstract: Wine tourism is one of the best opportunities for rural development, but because it is partially exposed to climatic conditions, it is a climate-vulnerable tourism activity. However, an understanding of the potential impacts of global climate change on this popular activity remains limited. This study proposes a new methodology that combines current daily gridded climate data from the E-OBS project with big spatiotemporal data from the Flickr photo-sharing platform through a generalized additive model This met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The agritourism owners had divergent views on whether climate change was going to be beneficial to their agritourism enterprises. The expansion of the previously summeronly season to all-year agritourism opening echoes the findings that the shoulder seasons are becoming holiday seasons [12,[43][44][45]. However, this is not an unmitigated success as the unpredictable weather leads to cancellations, in all seasons (R2).…”
Section: How Does Climate Change Affect the Agritourism Business For ...mentioning
confidence: 75%
See 2 more Smart Citations
“…The agritourism owners had divergent views on whether climate change was going to be beneficial to their agritourism enterprises. The expansion of the previously summeronly season to all-year agritourism opening echoes the findings that the shoulder seasons are becoming holiday seasons [12,[43][44][45]. However, this is not an unmitigated success as the unpredictable weather leads to cancellations, in all seasons (R2).…”
Section: How Does Climate Change Affect the Agritourism Business For ...mentioning
confidence: 75%
“…Despite there now being a scientific consensus that the planet is warming [9], Fourment et al's [10] recent work exploring wine growers' perception of climate change still found scepticism on this topic. Notwithstanding this example of an unwillingness to face the truth, there is a broader swathe of research, dating back to at least 2005 [11] and up to the present day [12], exploring how climate change is affecting wine growing and its interrelated tourism. Climate change has been demonstrated to have an impact worldwide on winemakers [11], [13],…”
Section: Climate Change-perception Reality and Adaptation In Viticulturementioning
confidence: 99%
See 1 more Smart Citation
“…GAMs provide more flexibility than GLMs, as the former relax the assumption of linearity while retaining coherent inference between the dependent and independent variables (Reiss 2006 ). Thus, GAMs are widely used in examining the associations between meteorological factors and tourism (Fotiadis et al 2021 ; Saenz-de-Miera and Rosselló 2014 ; Sottini et al 2021 ; Tiwari et al 2021 ; Yoon 2019 ) owing to their ability to describe static nonlinearities, i.e. nonlinear effects that are stable over time (Aldrin and Haff 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies, such as Marlowe and Lee (2018), showed that the designations of the origin of wines are a joint representation directly related to the development's production, quality of the environment's geographical characteristics, and the local terroir. The set also contains destination image studies to generate rural development (Iatisin et al, 2018;Sottini et al, 2021) and studies on the sustainable use of natural resources by wineries and wine tourism (e.g., Martins et al, 2017;Serra-Cantallops et al, 2021;Sun & Drakeman, 2020). The research points out cooperation to achieve sustainable goals and create a wine tourism destination image, but also a coopetition for resources among the two industries, wine, and tourism.…”
Section: Thematic Relevance and Development Matrix Of Wine Tourism St...mentioning
confidence: 99%